Ndonga'zibomvu: appropriation of public space: designing an oral resource centre to appropriate public space within the colonial context of Pietermaritzburg - Monaheng, Rethabile (My University, 2018)
‘Ndonga zibovu’, as Pietermaritzburg is known, is a statement to the striking red brick buildings of the colonialist era, designed to be reminiscent of Victorian era London. The city was founded by the Voortrekkers in 1838 (Kzn.co.za, 2018), and named after prominent members of the Voortrekker community. It is the ‘perfect Apartheid city’ by design; the city at the centre, industry and factories forming a ‘buffer’ and segregated racial groups on the outskirts. These divisions are still present today, much like many South African towns and cities. There is a deep history and memory associated within the city. Places that hold good and bad memories of the past. Places and spaces which, even today, evoke a certain feeling to the user. The city centre was one such place, which restricted and limited access and mobility. It is from this point, and place, that I seek to develop an approach to civic architecture and public space that is more inclusive and accessible to all, one which confronts the past, and redefines the space. Appropriation of public space is important in re-identifying with a space. Pietermaritzburg has a rich history. Parts of which are documented in the Voortrekker Museum and Natal Museum. These parts which are not documented, those which are missing; those are the parts of the history of Pietermaritzburg I wish to bring to light and celebrate. A city that celebrates it’s history and heritage to such a vast degree, has only celebrated the colonial history in which it still identifies with.